ANALISIS PROBLEMATIKA PEMAHAMAN MODERASI BERAGAMA SISWA MADRASAH TSANAWIYAH SWASTA SIDOARJO - Triana Rosalina Noor; Muhamad Ripin Ikwandi (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This qualitative research-case study uses observation; interviews and focus group discussions with principal of the madrasah, vice principal of curriculum, PAI teachers and fifteen students; and madrasah documentation studies as data collection. Data analysed by using fishbone analysis through problem identification, problem formalization and continued identification of causes. The research’s result show that the problem of understanding religious moderation of students at MTs Hidayatul Muta'allimiin Sidoarjo is mapped to six aspects namely Man, Money, Method, Material, Measurement and Environment. In human aspect was identified that the less role of principals, teachers and less parents’s role in socializing the implementation of religious moderation. In money aspect, lack of allocated funds became obstacles to provide religious moderation programs. In method aspect, there are still limited learning methods used in teaching religious moderation in the madrasah environment. In material aspect, less infrastructure making learning of religious moderation become monotonous without in-depth stimulation and contextual analysis. The measurement aspect shows that there has never been an evaluation of the understanding of religious moderation before. For environmental aspect, the monocultural environment in which some students live also plays a role in students' understanding of religious moderation, because a monocultural community environment makes students unaccustomed to interacting with individuals who have different views or backgrounds.